The study of training and development towards hotel employee job performance: a focus on 1 to 5 star hotels in Penang / Siti Zalipah Ibrahim - Ibrahim, Siti Zalipah (Faculty of Hotel and Tourism Management, 2015)
This research is conducted to study the impact of the training and development toward hotel employee job performance. In this research, a total of 382 respondents was deployed and as a result, 194 responses were successfully collected, representing 51% of the total sample. The data were analyzed using descriptive statistic, reliability analysis to test the reliability of the variables, correlation analysis to test the strength and direction of the relationship. Factor analysis is used to know the significant of each questions and regressions analysis to test the contribution and impacts of the variables or to examine the relationship between training and development and job performance. The finding reveals that training and development does influence job performance.